MONEY, BANKS, AND MONETARY POLICY (A SHARIA ECONOMIC LAW APPROACH) - Rumatiga, Hidayat; Janwari, Yadi; Hasanuddin, Muhammad (DE'RECHTSSTAAT, 2024)
Along with the dynamics of the global and domestic economy, the challenges faced by the monetary system are increasingly complex. The financial crisis, technological changes in payment systems, and developments in the global market have had a significant impact on the way money and banks operate. For example, the emergence of digital currencies and fintech has changed the traditional financial landscape, creating new opportunities and risks. This study aims to understand the relationship between money, banks, and monetary policy in the context of the Indonesian and Islamic economies. The methods used are the approach of revelation, the opinions of scholars, and fatwas as well as the results of other relevant research. The results of the study show that monetary policy is a policy made by Bank Indonesia in order to control the circulation of money so that it remains stable and aims to maintain the stability of the rupiah; maintain the stability of the payment system, and help maintain the stability of the financial system to support sustainable economic growth. The Prophet Muhammad SAW used two currencies, dinar (gold) and dirham (silver). The Prophet Muhammad established the dinar and dirham currencies as the monetary standards at that time. Where both types of currencies were adopted from Rome and Persia.